Exploring the Allure of Music for Gifted and Talented Students - Peter Ong; Ismail, Md Jais (MultiTech Publisher, 2023)
Gifted and talented children are potentially marginalized due to a lack of awareness in society. Gifted and talented students in schools are at high risk if their educational needs are not met which can cause them to experience burnout, emotional disturbances and psychological problems. This article discusses explicitly the importance of music for gifted and talented students so that they can raise awareness among teachers, parents and the community. The analysis results from various literatures show that the role of music is so important in shaping and supporting positive emotions among gifted students, in fact it helps sharpen their gifted traits.